A new strategy for porous carbon synthesis: Starch hydrogel as a carbon source for Co3O4@C supercapacitor electrodes. Issue 6 (15th March 2022) - He, Liwen; Lin, Chen; Zhao, Yican; Gao, Wenhai; Zhang, Hailian; Lin, Bizhou; Sun, Dongya
Abstract: A novel Co3 O4 @C composite with a three-dimensional (3D) interconnected network morphology was successfully fabricated by anchoring cobalt oxide nanocrystals onto porous carbon originating from starch hydrogels via freeze drying, precarbonization and thermal treatment in an aqueous system. Benefiting from unique structural features, the optimized electrode delivers an excellent capacitance of 1314.0 F g −1 (1 A g −1 ) and outstanding durability in terms of capacity preservation (93.5% over 10, 000 cycles). In addition, an asymmetric supercapacitor consisting of DF-2 and active carbon exhibits an energy density of 149.1 Wh⋅kg −1 at 800 W kg −1 while maintaining great stability. The observed excellent performance is attributed to the unique 3D network, good conductivity and high surface-to-volumetric ratio of the carbon skeleton derived from the starch gel, which has wide scope for applications.